METHOD OF EARLY CHILDHOOD SEXUAL EDUCATION IN INDONESIA - Eti Rimawati; Sri Achadi Nugraheni (Jurnal Kesehatan Masyarakat Andalas, 2018)
The issue of violence or sexual abuse in children is one of the reproductive health problems facing Indonesia. Some efforts to provide early child sex education have been done through teachers, parents and children. This study aims to describe the method of sex education that has been done to improve early childhood understanding related to reproductive health. The review process is done by searching the results of research can be accessed through google scholar in the form of journals, proceedings and scientific thesis, with the keyword "early child sex education", early reproductive health education ". Data selection and data extraction are done manually and then analyzed narratively. Early childhood sex education methods have been done for parents and children. Media used in the form of modules, infographics and games by way of lecture through lectures, discussion / group communication and games. With the advent of the development of technology and digital media it is necessary to optimize the media as a medium of early child sex education.